Method for preparing SnO2-coated CuO reinforced silver-based composite material by using hydrothermal alloy and powder metallurgy method
The preparation of SnO2@CuO core-shell structure-enhanced silver-based composite material through hydrothermal synthesis and powder metallurgy has solved the technical bottlenecks of AgSnO2 electrical contact materials in arc erosion, temperature rise control, conductivity and microstructure control, achieved high density and excellent comprehensive performance, significantly improved the resistance to arc ablation and service life.
Patent Information
- Application Number
- CN202510077227.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-25
AI Technical Summary
The existing AgSnO2 electrical contact materials have technical bottlenecks in arc erosion, temperature rise control, conductivity and microstructure control, and it is difficult to completely replace the highly toxic AgCdO materials.
The SnO2@CuO core-shell structure-enhanced silver-based composite material was prepared by hydrothermal synthesis and powder metallurgy. High density and good comprehensive performance were achieved through multi-stage sintering and extrusion drawing processes, and the resistance to arc ablation and service life was significantly improved.
The high density and excellent comprehensive performance of SnO2@CuO enhanced silver-based composite materials are achieved, which significantly improves the resistance to arc ablation and service life, and meets or exceeds the performance requirements of traditional AgCdO materials.
Smart Images

Figure CN119876672A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to powder metallurgy and metal-based composite material preparation technology, relates to the field of new electronic information materials, and provides a method for preparing a core-shell structure SnO2@CuO reinforced silver-based composite material by using hydrothermal synthesis and powder metallurgy. Background Art
[0002] Among traditional electrical contact materials, AgCdO (silver-cadmium oxide) has long been widely used in low-voltage electrical appliances due to its good arc erosion resistance when switching on and off the arc, as well as relatively low contact resistance and good conductivity. In the application of AgCdO (silver-cadmium oxide), cadmium oxide decomposes in the local high-temperature arc zone and has a certain extinguishing or inhibiting effect on the arc, thereby reducing the risk of ablation and welding of the material. However, cadmium is a heavy metal with high toxicity. It is very easy to cause environmental pollution and health hazards during use, recycling and disposal, and faces many restrictions in terms of environmental protection and safety. Countries have successively formulated strict environmental protection regulations (such as the RoHS directive, etc.) to restrict or prohibit the use of cadmium-containing materials. Therefore, reducing or even removing cadmium while ensuring the reliability of electrical contact has become a consensus in the development of the new electronic information materials industry.
[0003] However, due to the toxicity of "cadmium", it faces many restrictions in terms of environmental protection and safety. AgSnO2 (silver-tin oxide) is considered to be the most promising low-voltage electrical contact material to replace AgCdO, but there is currently no method that can make the comprehensive performance of AgSnO2 (silver-tin oxide) completely match that of AgCdO. At present, the main preparation methods of AgSnO2 (silver-tin oxide) include internal oxidation method, powder metallurgy method, reaction synthesis method, etc. Among them, powder metallurgy method has become the most commonly used method for silver metal oxide electrical contact materials due to its advantages such as simple process and easy addition of components (such as dopants). However, no matter which method is used to prepare the AgSnO2 electrical contact material, there is currently no method that can make the comprehensive performance of AgSnO2 (silver-tin oxide) completely match that of AgCdO.
[0004] In the Ag-MeO9 (silver-metal oxide) system, SnO2 (tin dioxide) has relatively suitable hardness, melting point and chemical stability, and can partially play a role similar to CdO in electrical contact materials. Although many improvements have been made in the prior art, and various methods such as adding a small amount of other metal oxides and doping SnO2 (tin dioxide) have been used, the temperature rise of AgSnO2 (silver-tin oxide) during arc erosion and other problems have not been solved in the end. SnO2 (tin dioxide) can partially play a role similar to CdO in electrical contact materials. Under conditions such as arc high temperature and mechanical wear, SnO2 (tin dioxide) can provide certain enhancement, high temperature resistance and anti-oxidation support for Ag (silver matrix), although the effect is not as comprehensive as CdO (cadmium oxide), making AgSnO2 one of the most potential environmentally friendly alternative materials at present. No matter which method is used to prepare the AgSnO2 electrical contact material, it has not been able to completely replace the toxic AgCdO electrical contact material so far.
[0005] AgSnO2 (silver-tin oxide) still has technical bottlenecks in terms of arc erosion resistance, temperature rise control, and conductivity. First, the problem of arc erosion and ablation. During the on-off process of low-voltage electrical appliances, high-temperature and high-energy arcs will continuously impact electrical contact materials. For AgSnO2 (silver-tin oxide), the high temperature of the arc will cause the separation of SnO2 (tin dioxide) and Ag (silver matrix) at the interface, the decomposition or redistribution of SnO2 (tin dioxide) particles, and even melting or ablation. These phenomena will weaken the overall performance of the AgSnO2 (silver-tin oxide) material, such as increasing contact resistance and reducing conductivity, and ultimately affecting the stability and service life of the electrical contact. Second, the temperature rise is too high. Under the action of the arc, if the material cannot dissipate the heat or suppress the arc in time, local overheating will occur. AgSnO2 (silver-tin oxide) produces local overheating under the action of electric arc, which causes the material to be more seriously welded or ablated than AgCdO (silver-cadmium oxide), thereby shortening the service life or affecting the switch performance. Therefore, the current high temperature resistance and welding inhibition ability of AgSnO (silver-tin oxide) are not as good as AgCdO (silver-cadmium oxide). Third, the microstructure is difficult to control. AgSnO2 (silver-tin oxide) is a composite material composed of a silver (Ag) matrix and SnO2 (tin dioxide) particles. During the preparation process, SnO2 (tin dioxide) particles are prone to agglomeration and coarsening in the matrix. Particle agglomeration or coarsening will lead to uneven local tissue of the material, destruction of thermal and electrical conduction paths, and make it easier for the material to form heat accumulation points in an arc environment, further exacerbating ablation and welding. Good microstructure control is crucial to maintaining the performance of the material in a high temperature and high stress environment, but the optimization of the microstructure of AgSnO2 (silver-tin oxide) still needs further breakthroughs. Fourth, the modification effect has not yet met expectations. In order to overcome the above problems, prior art has attempted to dope other elements in SnO2 (tin dioxide) or add other oxides to the silver matrix, such as CuO, Bi2O3, In2O3, etc., or improve the preparation process (such as powder metallurgy, internal oxidation, reaction synthesis, etc.). Although these methods can improve the local performance of AgSnO2 (silver-tin oxide) to a certain extent, they have not yet fully reached or surpassed AgCdO (silver-cadmium oxide) in all key performance indicators. Especially in the arc switching environment with high load (high current, high power), the performance gap of AgSnO material is more obvious. Summary of the invention
[0006] (1) Purpose of the Invention
[0007] The core technical problem to be solved by the present invention is to take into account the controllable preparation of nano or submicron SnO2 particles when preparing silver-metal oxide composite electrical contact materials, and to form a core-shell structure with CuO to enhance interface bonding, and to achieve high density and good comprehensive performance through multi-stage sintering and extrusion drawing processes, thereby significantly improving the arc erosion resistance and service life.
[0008] The technical obstacle to be overcome by the present invention is the most core "bottleneck" technical difficulty when the AgSnO system replaces AgCdO, that is, the comprehensive breakthrough of the AgSnO system in the preparation process and organizational structure; the specific technical difficulties are divided into: when preparing silver-metal oxide composite electrical contact materials, realize the preparation of controllable nano or submicron SnO2 particles and ensure their uniform dispersion in the silver matrix; form a stable CuO core-shell structure on the surface of SnO2 particles to enhance the interface bonding force between SnO and the silver matrix; through multi-stage sintering and extrusion drawing process, achieve high density and excellent comprehensive performance of the material; significantly improve the material's arc erosion resistance and service life to meet or exceed the performance requirements of traditional AgCdO materials.
[0009] In order to solve the common problems and bottlenecks of the above-mentioned prior art silver-metal oxide electrical contact materials (especially the AgSnO2 system), the present invention provides a method for preparing SnO2@CuO reinforced silver-based composite materials by hydrothermal synthesis and powder metallurgy, that is, by the preparation method of "SnO2@CuO coating + multi-stage sintering + extrusion drawing", SnO2@CuO powder is obtained by hydrothermal synthesis, and then the SnO2@CuO reinforced silver-based composite material is prepared by traditional powder metallurgy technology, the interface bonding is improved by core-shell coating, and the density and organizational uniformity are improved by multi-stage sintering and subsequent plastic deformation, thereby greatly improving the material's arc erosion resistance and service life.
[0010] (2) Invention solutions for solving technical problems
[0011] The present invention provides a method for preparing SnO2@CuO reinforced silver-based composite material by hydrothermal synthesis and powder metallurgy, and the SnO2@CuO reinforced silver-based composite material is prepared by powder metallurgy preparation technology; the specific technical scheme is as follows:
[0012] The method for preparing SnO2@CuO reinforced silver-based composite material by hydrothermal synthesis and powder metallurgy method described in the present invention comprises the following four stages:
[0013] S1. Core material SnO2 powder: Use polyethylene glycol PEG as a template to prepare SnO2 powder, and prepare core material SnO2 powder; first, take tetrahydrofuran and deionized water, and prepare a solution according to a volume ratio of 2:1, then add 0.1-3 mol / L PEG, and stir until the solution becomes transparent to obtain a polyethylene glycol template solution; then take tetrahydrofuran and anhydrous ethanol, and prepare a solution according to a volume ratio of 1:1, and then add 1-5 mol / L SnCl4·5H2O and 3-20 mol / L urea, and stir to obtain a tin source solution; finally, use a burette to add the polyethylene glycol template at a rate of 5 ml each time and at intervals of 3-10s. The plate solution is added dropwise to the tin source solution, and the stirring is continued for 15-50 minutes, and the ultrasonic dispersion is performed for 10-30 minutes, and the ultrasonic frequency is 50Hz; the mixed solution is then transferred to a hydrothermal autoclave with a polytetrafluoroethylene liner, and reacted at 180°C in a forced air drying oven for 30-60 minutes; after the reaction is completed, it is naturally cooled to room temperature, the precipitated product is collected and centrifugally washed with deionized water and anhydrous ethanol for 5-10 times, and placed in a vacuum drying oven at 60°C for 5-12 hours, and the above powder is calcined at 300-800°C in a muffle furnace for 1-3 hours and then naturally cooled to room temperature to obtain SnO2 powder, and the particle size can be controlled at 50nm-1000nm.
[0014] S2. Deposition synthesis of shell material: generate Cu(OH)2 powder on the surface of SnO2 powder by hydrothermal method, and then calcine the Cu(OH)2 to obtain SnO2@CuO powder; put SnO2 powder and deionized water into a container in a ratio of 1:20, and stir magnetically for 15-30 minutes at 30°C. After stirring, add CuSO4 powder (SnO2:CuSO4=6:1), and continue stirring for 5-10 minutes until the mixture is evenly mixed; then use a pipette to drop N with a concentration of 40 mol / L at a speed of (10s / drop) aOH solution, after the solution pH reaches 7-9, continue stirring for 90-120 minutes, filter the supernatant, and then add anhydrous ethanol according to the volume ratio of the remaining gel solid state of 1:4 (remaining gel solid state: anhydrous ethanol = 1:4); then after 2-5 times of centrifugation and washing, a Cu(OH)2 blue precipitate is obtained, the precipitate is placed in a vacuum drying oven and dried at 100°C for 1-3h, then ground and sintered in a furnace at 100-850°C for 1-2h to finally obtain a black powder of SnO2@CuO, and the particle size can be controlled at 80nm-1100nm.
[0015] S3. Prepare composite powder: mix the SnO2@CuO powder and silver powder in proportion and ball mill; configure the SnO2@CuO powder and silver powder according to the ratio of 10%-18% (mass percentage) of SnO2@CuO in the silver matrix, and ball mill at a speed of 50-450r / min for 0.5-1.5h to obtain a uniformly mixed composite powder.
[0016] S4. Forming and sintering: The composite powder is loaded into a mold, formed under a pressing pressure of 200-600 MPa, and the formed ingot is placed in a sintering furnace, and sintered at 400-860°C for 3-6 hours to obtain a SnO2@CuO reinforced silver-based composite material sintered billet; finally, the sintered billet is densified, extruded, drawn or rolled into a wire or strip; the sintered billet is densified again, and extruded, drawn or rolled into a SnO2@CuO reinforced silver-based composite material wire or strip.
[0017] The present invention discloses a method for preparing SnO2@CuO reinforced silver-based composite material by hydrothermal synthesis and powder metallurgy, and the specific steps are as follows:
[0018] S1. SnO2 powder of core material: SnO2 powder is prepared by using polyethylene glycol PEG as a template to prepare SnO2 powder of core material;
[0019] S1.1 Prepare polyethylene glycol template solution: mix tetrahydrofuran and deionized water in a volume ratio of 2:1, add 0.1-3 mol / L polyethylene glycol PEG, and stir until the solution is transparent to obtain a polyethylene glycol template solution;
[0020] S1.2 Prepare a tin source solution: mix tetrahydrofuran and anhydrous ethanol in a volume ratio of 1:1, add 1-5 mol / L SnCl4·5H2O and 3-20 mol / L urea, stir evenly, and obtain a tin source solution;
[0021] S1.3 Mix the polyethylene glycol template solution and the tin source solution: Use a burette to add the polyethylene glycol template solution to the tin source solution at a rate of 5 ml each time and an interval of 3-10 seconds, continue stirring for 15-50 minutes, and then perform ultrasonic dispersion for 10-30 minutes at an ultrasonic frequency of 50 Hz;
[0022] S1.4 Hydrothermal synthesis reaction: transfer the mixed solution into a hydrothermal reactor with a polytetrafluoroethylene liner, react at 180°C for 30-60 minutes, cool naturally to room temperature after the reaction, collect the precipitated product and wash it with deionized water and anhydrous ethanol by centrifugation for 5-10 times, and dry it in a vacuum drying oven at 60°C for 5-12 hours until it is completely dry;
[0023] S1.5 Calcination treatment: Calcine the dried powder in a muffle furnace at 300-800°C for 1-3 hours, and cool it naturally to room temperature to obtain SnO2 powder with a particle size that can be controlled between 50nm and 1000nm;
[0024] S2. Deposition synthesis of shell material: Cu(OH)2 powder is generated by hydrothermal method on the surface of SnO2 powder, and then the Cu(OH)2 is calcined to obtain SnO2@CuO powder;
[0025] S2.1 Preparation of SnO2 powder suspension: Mix the SnO2 powder prepared in step (1) with deionized water in a ratio of 1:20 and stir magnetically at 30°C for 15-30 minutes;
[0026] S2.2 Add copper source copper sulfate (II) CuSO4 powder: Add CuSO4 powder, the mass ratio of SnO to CuSO4 is 6:1, and continue stirring for 5-10 minutes until the mixture is uniform;
[0027] S2.3 Adjust the pH value of the solution: add 40 mol / L NaOH solution at a rate of 10 seconds / drop with a pipette, slowly add one drop of NaOH solution with a pipette every 10 seconds, adjust the pH value of the solution to 7-9, and continue stirring for 90-120 minutes;
[0028] S2.4 Filter the supernatant: add anhydrous ethanol at a volume ratio of 1:4 between the remaining gel solid and anhydrous ethanol, centrifuge and wash 2-5 times to obtain a blue Cu(OH)2 precipitate;
[0029] S2.5 Drying and grinding: Dry the precipitate in a vacuum oven at 100°C for 1-3 hours;
[0030] S2.6 Sintering into a core-shell structure: After grinding, the powder is kept at 100-850°C in a sintering furnace for 1-2 hours, and finally cooled naturally to room temperature to obtain SnO2@CuO black powder with a particle size that can be controlled in the range of 80nm-1100nm;
[0031] S3. Preparation of composite powder: SnO2@CuO powder and silver powder are mixed according to the ratio of 10%-18% SnO2@CuO in the silver matrix, and ball milled at a speed of 50-450r / min for 0.5-1.5 hours to obtain a composite SnO2@CuO core-shell structure powder having a uniform mixture;
[0032] S4. Forming and sintering: The composite powder is loaded into a mold and formed at a pressing pressure of 200-600 MPa. The formed ingot is then placed in a sintering furnace and sintered at 400-860°C for 3-6 hours to obtain a SnO2@CuO reinforced silver-based composite material sintered billet. The sintered billet is then densified and extruded, drawn or rolled into a SnO2@CuO reinforced silver-based composite material wire or strip.
[0033] According to the above invention content, the preferred process of the present invention is:
[0034] Preferably, in the template method preparation of the present invention, the preferred addition amount of polyethylene glycol PEG in the polyethylene glycol template solution is 0.5 mol / L.
[0035] Preferably, in the template method, the preferred amount of SnCl4·5H2O added to the tin source solution is 3 mol / L, the preferred amount of urea added is 15 mol / L, and the particle size of the prepared SnO2 powder is preferably 350 nm.
[0036] Preferably, the particle size of the synthesized SnO2@CuO powder of the present invention is 450nm.
[0037] Preferably, the SnO2@CuO powder and the silver powder of the present invention are configured so that 14% SnO2@CuO is contained in the silver matrix, and the composite powder is obtained by ball milling at a rotation speed of 350 r / min for 1 h.
[0038] Preferably, the pressing pressure in the preparation of the composite powder of the present invention is selected to be 400 MPa.
[0039] Preferably, the ingot sintering temperature of the present invention selects multi-stage sintering, and the preferred sintering temperature and time are: 400°C (keeping for 1h) → 600°C (keeping for 1h) → 860°C (keeping for 1h); specifically including three stages:
[0040] First sintering: Keep at 400℃ for 1 hour, and microscopic particles will be bonded and connected to the neck locally;
[0041] Second sintering: Keep at 600℃ for 1 hour, the diffusion bonding between powders is deepened, the micropores inside the material are compressed and reduced, and the contact between particles is strengthened;
[0042] The third sintering: keep warm at 860℃ for 1 hour, the high temperature promotes the diffusion of a large number of atoms or ions to achieve more complete densification, greatly reduce the porosity, and form a uniform and stable reinforcement phase distribution.
[0043] Preferably, the density of the sintered blank of the present invention reaches 98% after densification, the extrusion temperature is 800° C., the extrusion pressure is 600 MPa, and finally the wire is drawn at room temperature.
[0044] (3) Technical principles included in this technical solution:
[0045] The technical solution of the present invention adopts a powder metallurgy preparation process to enhance the silver-based material using a core-shell structured SnO2@CuO composite material. In the present invention, SnO2 is used as a core material and CuO is used as a shell material to form a SnO2@CuO core-shell structure to enhance the comprehensive performance of the silver-based composite material.
[0046] First, the technical principle of core (SnO) preparation: From the perspective of materials science, the present invention realizes the controllable synthesis of SnO2 core by combining template method and hydrothermal synthesis method. The PEG template effectively controls the particle size and morphology of SnO2, while the hydrothermal synthesis method provides a uniform and adjustable synthesis environment. Finally, through calcination and post-treatment steps, high-purity, particle-size-controlled SnO2 nanopowder is obtained, which lays a solid foundation for the subsequent formation of CuO shell and the performance optimization of composite materials.
[0047] Polyethylene glycol (PEG) is used as a template to control the particle size. Polyethylene glycol (PEG) is a high molecular chain surfactant that can self-assemble in solution to form micelles or other ordered structures. These micelles act as "templates" in solution, regulating the nucleation and growth process of SnO2 through spatial restriction and interface effects. The hydrophilic and hydrophobic ends of the PEG molecule can interact with the SnO2 precursor to form a stable interface structure, restricting the free growth of SnO2 nanocrystals, thereby achieving precise control of the particle size. Furthermore, by adjusting the concentration of PEG, the number and size of micelles can be changed, thereby affecting the nucleation density and growth rate of SnO2 nuclei. A high concentration of PEG will form more template sites, promote the generation of more small nuclei, and ultimately obtain SnO2 powders with smaller particle sizes; conversely, a low concentration of PEG will reduce the template sites, allowing the nuclei to grow more freely and generate larger SnO2 particles. From the perspective of nucleation and growth dynamics, in the presence of PEG, the nucleation of SnO2 is limited by the template, and the balance between the nucleation rate and the growth rate determines the final particle size; by controlling the concentration of PEG and the reaction time, this balance can be adjusted to accurately control the particle size range of SnO2 (50nm-1000nm). From the perspective of surface energy and morphology control, PEG molecules change the surface energy distribution of the crystal through interaction with the SnO2 surface, thereby affecting the growth rate on different crystal planes; therefore, the regulation of surface energy helps to achieve morphology control of SnO2 crystals.
[0048] In the hydrothermal synthesis method, the dropwise reaction of solution A and solution B slowly decomposes and releases ammonia under hydrothermal conditions, adjusts the solution pH, and facilitates the hydrolysis and nucleation of SnO2. Solution A is a mixture of tetrahydrofuran (THF) and deionized water in a volume ratio of 2:1, and 0.1-3 mol / L PEG is added; therefore, solution A provides a PEG template and a suitable reaction medium, promoting the uniform nucleation of SnO2 and limiting crystal growth. Solution B is a mixture of tetrahydrofuran and anhydrous ethanol in a volume ratio of 1:1, and 1-5 mol / L SnCl is added as a 5HSOn source, and 3-20 mol / L urea is added as a slow-release ammonia source; urea decomposes under hydrothermal conditions to generate ammonia (NH) and carbon dioxide (CO), slowly adjusts the solution pH, and promotes the hydrolysis and nucleation process of SnO2. Further, solution A is added to solution B at a rate of 5 mL each time and at intervals of 3-10 seconds using a burette to ensure the slow release and uniform distribution of the precursor; this slow dripping method helps to control the local reaction concentration and avoid local oversaturation leading to uneven nucleation, thereby obtaining uniform SnO2 nanoparticles. Furthermore, after the dropwise addition reaction is completed, ultrasonic dispersion (frequency 50 Hz) is performed for 10-30 minutes. The mechanical energy of ultrasound can effectively break up the aggregated particles, promote the uniform dispersion of the precursor, and prevent the formation of large particles. In addition, ultrasound can also increase the kinetic energy of the solution, promote full contact between the reactants, improve the uniformity of the reaction and the dispersibility of the product; and the mixed solution is transferred to a hydrothermal autoclave with a polytetrafluoroethylene liner and reacted at 180°C for 30-60 minutes; under high temperature and high pressure, SnCl is hydrolyzed under · water 5H hot O conditions to generate SnO2 precursor. The hydrothermal environment promotes the rapid formation of crystal nuclei and the orderly growth of crystals, while ensuring the high purity and good crystallinity of SnO2.
[0049] Second, the technical principle of shell (CuO) preparation: In the present invention, the preparation of the CuO shell is achieved by combining precipitation and heat treatment to achieve uniform coating of CuO on the SnO2 core. This process not only ensures the uniformity and stability of the shell, but also gives the composite material excellent comprehensive properties.
[0050] From the formation of Cu(OH)2 shell by precipitation, the formation of Cu(OH)2 shell by precipitation has the advantages of providing copper ions (Cu 2+ ) and interface action. The technical solution of the present invention mixes SnO2 powder with CuSO4 solution, and CuSO4, as a copper precursor, dissociates in the solution to provide Cu 2+ ions; these copper ions will become the source of subsequent precipitation reactions and are evenly distributed on the surface of SnO2 powder and the surrounding environment. 2+The ions interact with each other, causing the copper ions to be enriched near the SnO2 surface, providing conditions for subsequent precipitation reactions; this interfacial enrichment effect contributes to the uniform deposition of Cu(OH)2.
[0051] The pH value of the solution needs to be adjusted to 7-9 from the solution mixing, and the pH value of the solution is gradually increased to 7-9 by slowly adding a 40 mol / L NaOH solution; this process requires precise control of the drop rate (10 seconds / drop) and the drop amount to avoid local over-alkalinization and non-uniform precipitation. Under neutral to slightly alkaline conditions, Cu 2+ Ion and OH - Ionic reaction generates Cu(OH)2 precipitate:
[0052] Cu 2+ +2OH - →Cu(OH)2↓
[0053] Among them, Cu(OH)2 as a precipitate tends to deposit on the surface of SnO2 particles to form a shell due to its nucleation effect on the SnO2 surface.
[0054] From the precipitation coating, due to Cu 2+ The ions are evenly distributed on and around the SnO2 surface, and the slow addition of NaOH allows the Cu(OH)2 precipitate to form evenly on the SnO2 surface. This uniform deposition is achieved by controlling the reaction conditions (such as the drop rate, pH value) and the reaction kinetics, ensuring consistent shell thickness and coverage. The slow precipitation process helps the Cu(OH)2 nuclei to grow in an orderly manner on the SnO2 surface, avoiding uneven or agglomerated precipitation caused by too fast a reaction.
[0055] From the heat treatment to the conversion to CuO, it undergoes drying and calcination, crystal structure and phase change. The Cu(OH) precipitate is placed in a vacuum drying oven and dried at 100°C for 1-3 hours. The main purpose is to remove the moisture in the precipitate to prevent cracks or uneven thermal expansion during high-temperature calcination. The dried Cu(OH) precipitate is then calcined in a sintering furnace at a temperature range of 100-850°C for 1-2 hours. The specific temperature and time depend on the required CuO phase purity and crystal structure. The chemical formula is:
[0056]
[0057] During the calcination process, Cu(OH) is dehydrated to generate CuO; this process not only removes water but also promotes the formation and growth of CuO crystals through high temperature.
[0058] From the perspective of phase change and crystallization, Cu(OH)2 is converted into CuO at high temperature, usually from microcrystalline or amorphous state to crystalline state. The choice of calcination temperature affects the grain size and crystal quality of CuO. Higher temperature and longer time are conducive to the growth of grains and the improvement of crystal structure. During the calcination process, CuO crystals are rearranged on the SnO2 surface to form a stable core-shell interface.
[0059] From the perspective of precipitation kinetics and thermodynamics, slow NaOH dripping controls the precipitation rate of Cu(OH)2, ensuring uniform deposition on the SnO2 surface; this precipitation kinetic control avoids local supersaturation and particle aggregation caused by rapid precipitation, ensuring the uniformity and consistency of the shell. CuO, as an oxide with high thermal stability, has good chemical stability and mechanical strength at high temperatures, and has strong interfacial bonding with SnO2, which can provide a stable reinforcement effect in the composite material. SnO2 and CuO achieve interfacial bonding through chemical bonds or physical adsorption. Good interfacial bonding ensures the stability of the core-shell structure and prevents the shell from peeling or falling off during subsequent processing (such as sintering and drawing). SnO2 and CuO have good compatibility in crystal structure and thermal expansion coefficient, reducing interfacial stress and potential interfacial defects. This helps to improve the mechanical strength and electrical conductivity of the composite material.
[0060] (4) Effects of the Invention
[0061] Compared with silver metal oxide prepared by traditional powder metallurgy, a metal oxide reinforced silver-based composite material with a SnO2@CuO core-shell structure was obtained; and the shell CuO was used as the connecting interface between SnO2 and silver, which improved the interfacial wettability of SnO2 and silver and improved the mechanical properties of the silver-based composite material.
[0062] First, precise particle size control. By using polyethylene glycol (PEG) as a template, the process can accurately control the particle size of SnO2 powder between 50nm and 1000nm. This controllability of particle size is crucial for the uniformity and performance optimization of the core-shell structure, ensuring that SnO2 as a core material has ideal dispersibility and reactivity in the composite material.
[0063] Second, efficient core-shell structure formation. The present invention adopts powder metallurgy technology to synthesize SnO2@CuO core-shell structure in steps, thereby achieving uniform coverage of CuO on the SnO2 surface. In the specific steps, the mixing ratio and reaction conditions of solution A and solution B are controlled by titration to ensure uniform deposition of Cu(OH)2 precursor on the SnO surface, and then converted into CuO by calcination to form a stable core-shell structure. This method improves the integrity and uniformity of the core-shell structure and avoids the problems of agglomeration and uneven coating.
[0064] Third, the performance of the composite material is enhanced. The technical solution of the present invention incorporates SnO2@CuO powder into a silver matrix at a ratio of 10%-18%, and prepares a composite material by ball milling and sintering. The introduction of the core-shell structure significantly enhances the mechanical properties and electrical conductivity of the silver-based composite material. SnO2@CuO, as a reinforcing phase, provides higher mechanical strength and thermal stability, while optimizing the conductive network of the silver matrix and improving the performance of the overall composite material.
[0065] Fourth, the realization of multifunctional composite materials. The SnO2@CuO reinforced silver-based composite material in the technical solution of the present invention not only has improved mechanical properties, but also exhibits excellent properties in electrochemical properties, catalytic activity and other aspects. The design of the core-shell structure enables the composite material to have multifunctional properties, broadening its application in the fields of electronics, energy, catalysis, etc. The present invention adopts process steps such as hydrothermal synthesis and low-temperature calcination, which reduces the use of organic solvents and energy consumption, and has high environmental friendliness. At the same time, the powder metallurgy technology is used to achieve efficient utilization and performance optimization of materials, reduce production costs, and improve economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS
[0066] Figure 1 A preparation process of SnO2@CuO reinforced silver-based composites by hydrothermal synthesis and powder metallurgy;
[0067] Figure 2 This is the extruded microstructure of the prepared SnO2@CuO reinforced silver-based composite material;
[0068] Figure 3 This is the macroscopic image of hydrothermally synthesized SnO2@CuO powder before calcination;
[0069] Figure 4 This is the metallographic image of SnO reinforced @Cu O silver-based composite material at 200 times magnification and 20μm scale;
[0070] Figure 5 This is the metallographic image of SnO reinforced Cu@O silver-based composite material at a magnification of 500 times and a scale of 10μm. DETAILED DESCRIPTION
[0071] The present invention provides a method for preparing SnO2@CuO reinforced silver-based composite materials by utilizing hydrothermal synthesis and powder metallurgy. Different from the common process route of "SnO2@CuO+multi-stage sintering+extrusion and drawing", the thermal conductivity and arc erosion resistance of the material are effectively improved, thus providing a feasible preparation method for AgCdO alternative materials.
[0072] The present invention is further described below in conjunction with the accompanying drawings and examples, but the protection content of the present invention is not limited to the scope described in the preparation examples and examples.
[0073] Figure 1 A process flow of preparing core-shell SnO2@CuO reinforced silver-based composites by hydrothermal synthesis and powder metallurgy is demonstrated, as shown in the following title:
[0074] The first step is to prepare SnO2@CuO powder: SnO2@CuO powder is obtained by combining electrolysis and sintering to synthesize powder materials with a composite structure;
[0075] The second step is to mix the SnO2@CuO powder and the silver powder in a certain proportion: the prepared SnO2@CuO powder and the silver powder are mixed in a certain proportion; this step is used to give the material specific electrical or mechanical properties;
[0076] The third step is to mix the powder evenly by ball milling: the above mixture is mixed by ball milling to ensure uniform distribution of ingredients and improve the uniformity and consistency of the material;
[0077] The fourth step is pressing and forming: pressing the evenly mixed powder into a shape, and forming a preliminary material shape through a mold to prepare for subsequent sintering;
[0078] The fifth step is sintering: the pressed material is sintered to combine the powder particles into a dense structure through high temperature heating;
[0079] Step 6: Subsequent processing (extrusion, drawing or rolling): The sintered material can be further processed into wire or strip by plastic processing methods such as extrusion, drawing or rolling. The final form of the material is suitable for different engineering applications.
[0080] Figure 2 The microstructure of SnO2@CuO reinforced silver-based composites in extruded state is shown at a magnification of 200 times.
[0081] Under 200 times magnification, the microstructural characteristics of SnO reinforced uO silver-based composite materials after extrusion are as follows:
[0082] From the perspective of the silver-based matrix structure, the grain morphology is that during the extrusion process, the grains of the silver matrix will be stretched along the extrusion direction, presenting a fibrous or columnar structure, which helps to improve the mechanical properties of the material, such as strength and ductility; it can be observed that the interface between the grains shows a relatively clear grain boundary, which helps the plastic deformation behavior of the material. From the perspective of the SnO2@CuO reinforcement phase, SnO nanoparticles or micron particles are uniformly dispersed in the silver matrix in the form of dots, flakes or lines. These good dispersions help to improve the overall performance of the composite material. The interface between the reinforcement phase and the silver matrix should show good bonding, and the interface bonding is tight, indicating that the reinforcement effect of the composite material is significant. From the perspective of the morphology and distribution of the reinforcement phase, the SnO2@CuO composite particles are uniform in morphology, which helps to improve the conductivity and mechanical properties of the material; especially Figure 2 The uniform distribution of the reinforcement phase in the silver matrix can be seen, which avoids particle agglomeration and ensures the consistency of the material. Figure 2 The overall microstructure reflects the effective reinforcement effect of SnO2@CuO reinforcement on the silver matrix, which is characterized by grain refinement and interface strengthening, which helps to improve the comprehensive properties of the material, such as electrical conductivity, mechanical strength and wear resistance.
[0083] Figure 3 The powder macrograph of the hydrothermally synthesized SnO@CuO composite material before calcination is shown, which helps to evaluate the preliminary quality of the material and the effectiveness of the preparation process. Figure 3 The SnO@CuO composite powder before calcination has the characteristics of uniform color, fine particles and good dispersion, which reflects the good dispersibility and composite effect of the material during the hydrothermal synthesis process, and lays the foundation for the subsequent calcination treatment and the improvement of the final performance.
[0084] In terms of color characteristics, SnO2 appears white or light gray, while CuO has dark brown to black color; Figure 3 The color of the SnO2@CuO composite powder in the experiment is between the two. The specific color is gray, which depends on the doping amount of CuO. The color distribution is uniform, which proves that the dispersion of SnO2 and CuO in the powder is relatively uniform. In terms of particle morphology and distribution, hydrothermal synthesis can usually produce uniform particles ranging from nanometers to micrometers. Figure 3In the macroscopic image, the powder presents a fine and uniform granular appearance; and the particles present a regular or approximately regular shape, such as spherical, cubic or flake, and good dispersibility makes the powder look loose and without obvious agglomeration. In terms of surface characteristics, the uncalcined powder presents a relatively smooth or slightly moist surface due to the action of water molecules in the hydrothermal synthesis process; the high-purity SnO2@CuO powder has uniform color and no obvious impurities or foreign matter. In terms of composite effect, the effective composite of SnO2 and CuO will be manifested as a coordinated unity of color and particle morphology on a macroscopic scale, reflecting the good compatibility and dispersibility of the two materials. The hydrothermal synthesis method described in the present invention can promote uniform mixing and crystallization of materials at a relatively low temperature, so the powder exhibits uniform and dense characteristics on a macroscopic scale.
[0085] Figure 4 It is a metallographic image of SnO2@CuO reinforced silver-based composite material (200 times magnification at 20μm scale), which clearly shows the microstructural characteristics of the core-shell synthesized SnO-reinforced silver-based composite material, reflecting the grain structure of the silver matrix, the morphology and distribution of the SnO-reinforced uO phase, and the interface bonding.
[0086] From the grain structure of the silver matrix, the grain size of the silver matrix can be clearly observed at 200 times magnification under a scale of 20μm; silver has a large grain structure, but due to the addition of SnO@CuO reinforcement phase, the grains are observed to be refined; the grain boundaries are clearly visible, showing the continuity and integrity of the grain boundaries, and the grain boundaries are fibrous or tensile, which is due to the directional growth of the grains caused by the stress applied during the extrusion process. From the distribution of the SnO2@CuO reinforcement phase, the SnO2@CuO reinforcement phase is distributed in the silver matrix in the form of dots, sheets or lines. In the metallographic image, the particle shape appears in these reinforcement phases as areas with different colors or brightness from the silver matrix; because it is a core-shell synthesized SnO2@CuO, composite particles with obvious boundaries can be seen on the core-shell structure, with SnO2 inside and SnO2 layer coated outside. In the SnO2@CuO reinforced silver-based composite material of the present invention, the SnO2@CuO reinforcing phase is evenly dispersed in the silver matrix, avoiding obvious agglomeration, which helps to improve the overall properties of the material, such as electrical conductivity and mechanical strength. Figure 4 There is no obvious uneven light and dark or particle agglomeration area. From the interface bonding, Figure 4 There is good interface bonding between the reinforcement phase and the silver matrix, and the interface is clear and has no obvious defects, indicating good compatibility between the two phases; there are no interface cracks, holes or unbonded areas.
[0087] From the perspective of comprehensive organizational characteristics, the presence of SnO2@CuO reinforcing phase helps to hinder the grain growth of the silver matrix, resulting in grain refinement, which can significantly improve the mechanical properties and conductivity of the material; the uniform distribution and good bonding of the reinforcing phase can effectively improve the comprehensive properties of the composite material, including conductivity, mechanical strength and wear resistance.
[0088] Figure 5 A metallographic image of SnO2@CuO reinforced silver-based composite material is shown (10μm scale, 500 times magnification), which clearly shows the microstructural characteristics of the core-shell synthesized SnO2@CuO reinforced silver-based composite material, reflecting the grain structure of the silver matrix, the morphology and distribution of the SnO2@CuO reinforcement phase, and the interface bonding.
[0089] Figure 5 In the figure, the 10μm scale and 500x magnification provide higher resolution observation conditions for analyzing the core-shell synthesized SnO2@CuO reinforced silver-based composites. From the distribution and uniformity of the reinforcement phase particles, the uniform distribution of the particles indicates that the material preparation process is well optimized. In terms of the distribution and morphology of the reinforcement phase (SnO@CuO), the SnO2@CuO reinforcement phase may be distributed in the silver matrix in the form of black or dark dots; when the image resolution is high (such as Figure 5 ) can be seen the uniformity of these particles; the uniform distribution indicates that the synthesis and preparation process is properly controlled; the spacing between the reinforcing phase particles is small and the distribution is uniform, which helps to improve the overall strength and conductivity of the composite material. Under 500 times magnification, the particle diameter is approximately below the micron level (less than 10μm); the refinement of the core-shell structure (SnO2 core, CuO shell) can improve the composite performance; SnO2 is the core and CuO is the shell, which is manifested as the brightness difference between the core and the boundary of the particle. From the perspective of the bonding between the reinforcing phase and the matrix, clear interface and defect-free distribution are the key. From the grain structure of the matrix (silver), the silver matrix appears as equiaxed grains, and its size can be measured by comparing the 10μm scale; the bonding strength and interface bonding between the silver matrix and the SnO@CuO particles are good, and the boundary between the particles and the matrix should be clearly visible, without cracks or holes. From the perspective of the matrix grain refinement and strengthening effect, the particles hinder the growth of grains and improve the mechanical properties of the silver-based composite material. The SnO2@CuO reinforcement phase can improve the strength, wear resistance and creep resistance of the composite material through the "second phase strengthening" mechanism; the reinforcement phase with refined particles and uniform distribution plays an effective pinning role in the matrix, preventing the matrix grain boundary sliding, thereby improving the strength of the material.
[0090] Preparation Example 1: Preparation method of a metal oxide reinforced silver-based composite material with SnO2@CuO core-shell structure
[0091] Step (1) Core material (SnO2): Preparation of SnO2 powder
[0092] The template method was adopted, with polyethylene glycol (PEG) as the template, and SnO2 powders of different sizes were prepared by a hydrothermal method, especially by controlling the reaction conditions (such as reaction temperature, time, PEG concentration, etc.) to provide the "core" material (SnO2) for the subsequent "core-shell" structure.
[0093] The specific steps include:
[0094] (1) Prepare solution A (polyethylene glycol template solution): tetrahydrofuran and deionized water in a volume ratio of 2:1, add 0.1-3 mol / L PEG, and stir until transparent;
[0095] (2) Prepare solution B (tin source solution): tetrahydrofuran and anhydrous ethanol in a volume ratio of 1:1, add 15 mol / L SnCl4·5H2O and 320 mol / L urea, and stir evenly);
[0096] (3) A (polyethylene glycol template solution) was slowly added to solution B (tin source solution) by titration, 5 ml each time, with an interval of 3-10s, and continuous stirring and ultrasonic dispersion, followed by reaction in a hydrothermal autoclave. Finally, SnO2 powder with controllable particle size (50nm-1000nm) was obtained by washing, drying and calcination.
[0097] Step (2) Deposition of shell material (CuO): Synthesis of SnO core@Cu shell O powder
[0098] Using the hydrothermal method, Cu(OH)2 is deposited on the surface of SnO2 powder, and then converted into CuO by calcination to form a SnO2@CuO core-shell structure. The specific steps include:
[0099] Mix SnO2 powder and deionized water in a ratio of 1:20 and stir;
[0100] Add CuSO4 powder (SnO2:CuSO4=6:1) and continue stirring evenly;
[0101] Slowly add 40 mol / L NaOH solution to make the solution pH reach 7-9, continue stirring and filtering to obtain Cu(OH)2 precipitate;
[0102] The Cu(OH)2 precipitate is dried, ground, and calcined in a sintering furnace at 100-850°C for 1-3 hours to finally obtain a black powder of SnO2@CuO (the particle size can be controlled at 80nm-1100nm).
[0103] Step (3) Mixing and ball milling of SnO2@CuO powder and silver powder
[0104] In order to prepare silver-based composite materials, SnO2@CuO core-shell powder needs to be evenly dispersed in silver powder.
[0105] Weigh according to the formation of 10%-18% (mass fraction) SnO2@CuO in the silver matrix (e.g. 14%);
[0106] The mixture is ball-milled at a speed of 50-450 r / min for 0.5-1.5 h (such as 350 r / min for 1 h) to obtain a uniformly mixed composite powder.
[0107] The core-shell structure is reflected in the ball milling process: the SnO2@CuO core-shell particles are only fully mixed with the silver powder, and the core-shell structure of SnO2@CuO will not be destroyed; it ensures that in the subsequent forming and sintering process, the core-shell powder can be dispersed into the silver matrix, thereby playing a reinforcing role.
[0108] Step (4) Pressing, sintering and extrusion (drawing or rolling) forming
[0109] The mixed powder was pressed, sintered and subsequently plastically deformed by powder metallurgy to prepare a high-density, high-performance SnO2@CuO / silver-based composite material.
[0110] Pressing: Pressing into blanks at a pressure of 200-600MPa (e.g. 400MPa);
[0111] Sintering: Sintering in multiple stages at 400-860℃ for 3-6h (e.g. 400℃ for 1h → 600℃ for 1h → 860℃ for 1h) to form a dense sintered blank;
[0112] Extrusion, drawing or rolling: The sintered billet is densified (density reaches 98%), extruded at about 800℃ and 600MPa, and finally drawn into wire (or strip) at room temperature.
[0113] The core-shell structure shows:
[0114] During the sintering process, the SnO2@CuO core-shell structure is tightly bonded to the silver matrix;
[0115] Since the interface bonding strength between CuO and SnO2 is good, and the CuO shell and the silver matrix can also produce a good interface effect, the electrical and mechanical properties of the composite material are further improved;
[0116] During the entire pressing-sintering-extrusion-drawing process, the core-shell structure is maintained and a uniformly dispersed reinforcement phase is formed in the silver matrix.
[0117] Preparation Example 2: Preparation method of core material (SnO2): Obtaining SnO2 oxide particles with controllable particle size and uniform dispersion in a silver matrix
[0118] The present invention uses the PEG template method + hydrothermal synthesis to accurately control the SnO2 particle size (optionally in the range of 50nm-1000nm) and reduce agglomeration, which is helpful to achieve uniform distribution in the subsequent ball milling and sintering processes, thereby solving the problem in the conventional preparation process that the SnO2 particle size is large and easy to agglomerate, resulting in uneven material microstructure and damaged conductive / thermal conduction paths.
[0119] The specific steps for preparing the core material (SnO2): SnO2 powder are as follows:
[0120] S1. Prepare solution A (polyethylene glycol template solution):
[0121] S1.1 Prepare a mixed solution of tetrahydrofuran and deionized water: first prepare a solution of tetrahydrofuran and deionized water in a volume ratio of 2:1, then measure the required volume of tetrahydrofuran and deionized water and add them to a clean beaker;
[0122] S1.2 Adding polyethylene glycol (PEG): according to the required polyethylene glycol (PEG) concentration, take 0.1-3 mol / L polyethylene glycol, and slowly add the polyethylene glycol (PEG) to the mixed solution of tetrahydrofuran and deionized water;
[0123] S1.3 Stir until the solution becomes transparent: Use a magnetic stirrer or a mechanical stirrer to continuously stir the solution until the solution becomes transparent to obtain a transparent solution A (polyethylene glycol template solution).
[0124] S2. Prepare solution B (tin source solution):
[0125] S2.1 Prepare a mixed solution of tetrahydrofuran and anhydrous ethanol: Take tetrahydrofuran and anhydrous ethanol, and prepare a solution in a volume ratio of 1:1. Then, add tetrahydrofuran and anhydrous ethanol in proportion, add them to another clean beaker, and mix thoroughly;
[0126] S2.2 Adding tin source and urea: Then add 1-5 mol / L tin tetrachloride (SnCl4·5H2O) and 3-20 mol / L urea, and then slowly add tin tetrachloride (SnCl4·5H2O) and urea to the mixed solution of tetrahydrofuran and anhydrous ethanol, while constantly stirring until completely dissolved, to form solution B (tin source solution);
[0127] S3. Mix solution A (polyethylene glycol template solution) and solution B (tin source solution):
[0128] S3.1 Add solution A (polyethylene glycol template solution) to solution B (tin source solution): Use a burette to add solution A (polyethylene glycol template solution) to solution B (tin source solution) at a rate of 5 ml each time and at intervals of 3-10 seconds. During the addition process, the time interval between each addition is 3-10 seconds to ensure uniform mixing.
[0129] S3.2 Continuous stirring: During and after the dropwise addition, continue stirring the mixed solution for 15-50 minutes to promote the full reaction;
[0130] S3.3 Ultrasonic dispersion: The mixed solution was subjected to ultrasonic treatment for 10-30 minutes at a frequency of 50 Hz to ensure uniform dispersion of the particles;
[0131] S4. Hydrothermal reaction:
[0132] S4.1 Transfer to hydrothermal autoclave: Transfer the mixed solution after ultrasonic dispersion to a hydrothermal autoclave lined with polytetrafluoroethylene to prevent adverse reactions between the solution and the autoclave wall;
[0133] S4.2 Hydrothermal reaction conditions: Place the hydrothermal reactor in a forced air drying oven preheated to 180°C, and then react at 180°C for 30-60 minutes to ensure that the reaction proceeds fully;
[0134] S4.3 Natural cooling: After the reaction is completed, take the hydrothermal kettle out of the drying oven and place it at room temperature to cool naturally to room temperature;
[0135] S5. Collecting and washing products:
[0136] S5.1 Collecting the precipitated product: centrifuging the precipitate in the cooled mixed solution through a centrifuge;
[0137] S5.2 Multiple washing: Wash the precipitate with deionized water and anhydrous ethanol, centrifuge after each washing, and repeat the washing 5-10 times to remove impurities;
[0138] S6. Vacuum drying treatment: the washed precipitate is placed in a vacuum drying oven and dried at 60°C for 5-12 hours until completely dry;
[0139] S7. Calcination treatment:
[0140] S7.1 Muffle furnace calcination: Place the dried powder in a muffle furnace, and then calcine the powder at 300-800°C for 1-3 hours in the muffle furnace and then naturally cool to room temperature to obtain SnO2 powder (particle size can be adjusted between 50nm and 1000nm);
[0141] S7.2 Natural cooling: After the calcination is completed, take out the muffle furnace and place it at room temperature to cool naturally to room temperature;
[0142] S8. Obtain the core material product: SnO2 powder, whose particle size can be controlled between 50nm-1000nm according to the calcination conditions (temperature and time).
[0143] Preparation Example 3: Preparation method of shell material (CuO) deposition: generate Cu(OH)2 powder, enhance the interface bonding strength between SnO2 and silver matrix, and improve thermal conductivity, electrical conductivity and arc ablation resistance
[0144] The present invention adopts the core-shell structure of "SnO2@CuO", that is, the CuO layer can form a good metallurgical bond with the silver matrix during the sintering stage (generating a trace amount of Cu-Ag solid solution or interface compound), thereby improving the overall electrical conductivity, thermal conductivity and arc erosion resistance of the composite material, and solving the problem that pure SnO is easy to loosen or stratify with the Ag silver matrix under high-temperature arc, resulting in performance degradation.
[0145] Preparation of core material (SnO2): The specific steps for synthesizing SnO core@Cu shell O powder are as follows:
[0146] S1. Preparation of SnO powder suspension:
[0147] S1.1 Weigh and mix SnO2 powder and deionized water: Put the SnO2 powder prepared in (1) and deionized water into a container in a ratio of 1:20.
[0148] That is, 20 grams of deionized water need to be added to 1 gram of SnO2 powder to ensure that the SnO2 powder is evenly dispersed in the water to form a stable suspension and avoid powder agglomeration;
[0149] S1.2 Magnetic stirring: Stir the SnO powder suspension at a constant temperature of 30°C with a magnetic stirrer for 15-30 minutes to fully disperse the SnO particles and ensure the uniformity of the SnO powder suspension; 30°C is a suitable temperature that helps improve stirring efficiency and avoid uncontrolled chemical reactions caused by high temperature;
[0150] S2. Add copper source copper sulfate (II) CuSO4 powder:
[0151] S2.1 Weigh and proportion copper (II) sulfate: According to the mass ratio of SnO2 to CuSO4 of 6:1, weigh an appropriate amount of CuSO4 powder, that is, 6 grams of SnO corresponds to 1 gram of CuSO4, so the mass ratio of SnO to CuSO4 of 6:1 ensures sufficient Cu 2+ ions participate in the reaction to form the desired Cu(OH) precipitate;
[0152] S2.2 Add copper (II) acid CuSO4: Slowly add CuSO4 powder to the SnO2 suspension, avoiding adding a large amount at one time to prevent uneven precipitation due to excessive local concentration;
[0153] S2.3 Magnetic stirring: Continue magnetic stirring at 30 °C for 5-10 minutes until the CuSO powder is completely dispersed and evenly mixed with the SnO suspension to ensure that the Cu 2+ The ions are evenly distributed in the suspension, ready for the subsequent precipitation reaction;
[0154] S3. Adjust the pH value of the solution:
[0155] S3.1 Add NaOH solution: Use 40 mol / L NaOH solution and slowly add it to the NaOH solution with a pipette at a rate of one drop every 10 seconds. Add NaOH solution drop by drop until the pH value of the NaOH solution reaches between 7 and 9 to ensure uniform precipitation and high purity of Cu(OH)2.
[0156] S3.2 Continuous stirring: After reaching the target pH value of 7-9, continue stirring at 30°C for 90-120 minutes to promote the 2+ Ions and OH - ions to generate Cu(OH)2 precipitation, while maintaining the stability of SnO2 to prevent it from participating in unnecessary reactions or precipitation;
[0157] S4. Separation and washing of precipitate:
[0158] S4.1 filtering the supernatant: filtering the reaction mixture to separate the supernatant and the lower gel precipitate, thereby removing the unreacted supernatant and retaining the Cu(OH)2 gel precipitate in the lower layer;
[0159] S4.2 Adding anhydrous ethanol: adding anhydrous ethanol in a volume ratio of 1:4 to the remaining gel solid, i.e., adding 4 parts of anhydrous ethanol to 1 part of the gel solid, thereby further purifying the precipitate by adding anhydrous ethanol to remove impurities dissolved in water and unreacted substances;
[0160] S4.3 Centrifugal washing: After 2-5 times of centrifugal washing, a blue Cu(OH)2 precipitate is obtained. An appropriate amount of anhydrous ethanol or other suitable solvent is used each time to ensure the purity of the precipitate (Cu(OH)2), remove residual impurities and unreacted substances, and improve the quality of the obtained product SnO core@C shell uO powder;
[0161] S5. Drying and grinding:
[0162] S5.1 Drying: Place the obtained Cu(OH)2 precipitate in a vacuum drying oven and dry it at 100°C for 1-3 hours to remove moisture;
[0163] S5.2 Grinding: Grinding the dried precipitate to obtain a uniform powder;
[0164] S6. Sintering into core-shell structure:
[0165] S6.1 Sintering: The ground powder is placed in a sintering furnace and sintered at a temperature range of 100-850°C for 1-2 hours. Through the sintering process, the CuO forms a core-shell structure on the surface of SnO2 to enhance the performance of the composite material. During the entire sintering process, Cu(OH)2 is converted into CuO and a uniform CuO core-shell structure is formed on the surface of SnO2.
[0166] S7. Obtain the core-shell structure material product: the product after sintering is black SnO powder@CuO, and its particle size can be controlled between 80 nanometers and 1100 nanometers.
[0167] Preparation Example 4: Preparation method of mixing SnO2@CuO powder with silver powder and ball milling: high density is obtained through reasonable sintering and plastic deformation process, and particle growth, agglomeration and pore defects are suppressed
[0168] The multi-stage step-by-step sintering (400°C → 600°C → 860°C) and subsequent extrusion and drawing proposed in the present invention can first eliminate some pores at a relatively low temperature, and then achieve grain diffusion and densification in the high temperature stage, while preventing SnO2@CuO from excessive growth or insufficient sintering, thereby obtaining a high-density (≥98%) and microstructured composite material, which solves the problem of high porosity, particle coarsening or agglomeration, etc., which is prone to occur in simple one-step sintering, making it difficult to improve the comprehensive performance of the material.
[0169] The specific steps of mixing and ball milling SnO2@CuO powder and silver powder are as follows:
[0170] S1. Ingredients:
[0171] S1.1 Ingredients ratio: generate 10%-18% (mass fraction) SnO2@CuO core-shell powder in the silver matrix as required. If the designed content is 14%, weigh it according to the ratio of 86% silver powder and 14% SnO2@CuO core-shell powder;
[0172] S1.2 Loading: Load the weighed silver powder and SnO2@CuO core-shell powder into the ball mill. According to actual needs, the ball mill can be made of cemented carbide, zirconium oxide, stainless steel and other materials, and matched with ball milling media (balls) of the same or compatible materials. A small amount of dispersant (such as a small amount of alcohol, organic solvent, etc.) can be added before or during loading to reduce powder agglomeration.
[0173] S2. Ball milling: ball milling at a speed of 50-450r / min for 0.5-1.5h (such as 350r / min for 1h) to obtain a uniformly mixed composite powder. In this stage, wet ball milling is used, and the solvent is kept stable during the ball milling process; if dry ball milling is used, it should be sealed to prevent dust from flying; after the ball milling is completed, the powder mixture in the ball milling tank is taken out;
[0174] S3. Drying: If wet ball milling is used, it needs to be dried (e.g., dried at 60–80°C) and appropriately sieved to remove large particles or agglomerates;
[0175] S4. Obtain the product: a composite powder of uniformly mixed "silver powder + SnO2@CuO core-shell particles".
[0176] Preparation Example 5: Preparation method of pressing, sintering and extrusion (drawing or rolling): While ensuring the high density and wear resistance / ablation resistance of the material, it also takes into account its easy processability (can be prepared into wire or strip)
[0177] The present invention achieves a balance between mechanical properties and processing properties by optimizing pressing, sintering pressure and temperature gradient, and combining high-temperature extrusion with room-temperature drawing, solving the problem that the material hardness is too high or sintered excessively in the traditional process, and the later mechanical processing (such as extrusion, drawing) will face cracking or difficult processing; on the contrary, if the density is insufficient, the performance will be unstable. The resulting product has a fine and uniform structure and excellent comprehensive properties, including high strength, conductivity and wear resistance, which can meet the needs of electrical contact materials for high-strength and high-conductivity materials.
[0178] The specific steps of pressing, sintering and rolling to prepare the strip are as follows:
[0179] S1. Composite powder pressing → compact (ingot): The SnO2@CuO composite powder prepared in the above steps is loaded into a mold and pressed at a pressing pressure of 200-600MPa to obtain an ingot (also called a compact); the resulting compact (ingot) has a regular shape and is a preliminarily formed SnO2@CuO reinforced silver-based composite green body, which is not yet dense;
[0180] S2. Sintering in stages: The obtained compact (ingot) is placed in a sintering furnace for multi-stage heating and sintering. The overall sintering time is about 3-6 hours (including heating and insulation time). Ensure sufficient insulation at each stage, so that the mechanism in the corresponding temperature range can proceed smoothly, and avoid premature or insufficient sintering leading to unstable performance.
[0181] S2.1 First sintering: The pressed green sheet (ingot green sheet) is placed in a sintering furnace, heated to 400°C, and kept warm for 1 hour. At this time, at a relatively low temperature, microscopic particle bonding and neck connection occur locally, promoting subsequent sintering at a higher temperature. At this time, organic matter or volatile impurities can basically decompose or volatilize when heated to 400°C, and escape through the pores inside the green sheet. Although the temperature of 400°C is not high, the atoms on the surface of the powder still have a certain activity and begin to diffuse at the micro-contact, promoting the growth of the primary neck.
[0182] S2.2 Second sintering: The sintered blank obtained by the first sintering is further heated to 600℃ and kept warm for 1h. At this time, the diffusion bonding between the powders is deepened, the micropores inside the material are further compressed and reduced, and the contact between the particles is strengthened. The grain boundaries are further formed and stabilized, laying a good foundation for subsequent high-temperature diffusion. At this time, in the temperature range of 600℃, the silver-based and doped SnO2 and CuO particles have higher diffusion rates, the atomic or ion migration is active, the solid-phase sintering diffusion mechanism is strengthened, the sintering neck grows rapidly, and with the increase of diffusion channels and the decrease of grain boundary energy, the pores continue to shrink, the densification is accelerated, and the mechanical strength of the material continues to increase.
[0183] S2.3 Third sintering: The sintered blank obtained by the second sintering is heated to 860°C again and kept at this temperature for 1 hour; the high temperature promotes the diffusion of a large number of atoms or ions to achieve more complete densification and greatly reduce the porosity; the SnO2 and CuO nano or submicron particles can be better combined with the silver matrix at this high temperature, which is conducive to the formation of a uniform and stable reinforcement phase distribution; at this time, in the temperature range of 860°C, both the silver matrix and the oxide particles undergo strong body diffusion and grain boundary diffusion, which promotes the growth of the sintered neck to fullness and closes most of the remaining pores, and the CuO part reacts microscopically with the silver matrix or SnO2 or forms an interface transition layer (interface reaction or local solid solution), which improves the overall bonding strength, so that the local diffusion of the component elements can be further evenly distributed and the segregation phenomenon can be reduced;
[0184] S3. High temperature and high pressure densification extrusion: the sintered blank is placed in a hot extrusion device and extruded at about 800°C with an extrusion pressure of about 600MPa; the internal pores of the material are further reduced by high temperature and high pressure to improve the density of the material; the density of the sintered blank after this step can reach about 98%; the high-density SnO2@CuO reinforced silver-based composite material rod (or other blank shape suitable for subsequent processing) obtained by hot extrusion of the obtained dense rod (or billet) has significantly improved strength and density;
[0185] S4. Room temperature drawing (or rolling): The dense rod obtained by hot extrusion is further reduced in diameter or thinned by drawing (or rolling) at room temperature to obtain a wire (or strip) of the desired shape and size;
[0186] S5. Final product: SnO2@CuO reinforced silver-based composite material wire (or strip), the material shape can be wire-like or strip-like, the tissue distribution is more uniform, and it has high strength, high conductivity and good wear resistance.
[0187] Example 1: SnO2@CuO fine particles + 12% content + high density, high pressure and high temperature sintering, the highest comprehensive balance
[0188] Example 1 mainly obtains a silver-based composite material with a core-shell structure (SnO2@CuO) and uniformly dispersed in a silver matrix through the overall process route of "hydrothermal preparation of SnO2 core → in-situ coating of CuO shell → mixing with silver powder for molding and sintering".
[0189] Step (1) Preparation of SnO2 powder: Figure 1 The process flow of the specific embodiment 1 is as follows: (1) Using polyethylene glycol (PEG) as a template to prepare SnO2 powder of different sizes. First, tetrahydrofuran and deionized water are prepared into a solution according to a volume ratio of 2:1, and then 0.5 mol / L of PEG is added and stirred to make the solution transparent to obtain solution A. Tetrahydrofuran and anhydrous ethanol are prepared into a solution according to a volume ratio of 1:1, and then 3 mol / L of SnCl4·5H2O and 15 mol / L of urea are added and stirred to obtain solution B. Finally, solution A is added dropwise to solution B with a burette at a rate of 5 ml each time and at intervals of 3 s, and stirring is continued for 15 min, and ultrasonic dispersion is performed for 10 min (ultrasonic frequency is 50 Hz). Finally, the mixed solution was transferred into a hydrothermal autoclave with a polytetrafluoroethylene liner and reacted at 180°C in a forced air drying oven for 30 minutes. After the reaction, it was naturally cooled to room temperature. The precipitated product was collected and washed by centrifugation with deionized water and anhydrous ethanol for 5 times, and dried at 60°C in a vacuum drying oven for 8 hours. The above powder was calcined at 400°C in a muffle furnace for 2 hours and then naturally cooled to room temperature to obtain SnO2 powder (particle size can be controlled at 200nm).
[0190] The product obtained in step (1) is SnO2 powder with a particle size controllable at 200 nanometers.
[0191] Step (2) Preparation of SnO2@CuO core-shell powder:
[0192] The SnO2 powder prepared in (1) and deionized water were placed in a beaker at a ratio of 1:20 and magnetically stirred for 15 min at 30°C. After stirring, CuSO4 powder (SnO2:CuSO4=6:1) was added and magnetically stirred for 5 min until the mixture was uniformly mixed. The beaker was then placed in an ultrasonic cleaner for 10 min. Finally, a 40 mol / L NaOH solution was added dropwise using a pipette at a speed of (10 s / drop). After the solution pH reached 7, stirring was continued for 90 min, the supernatant was filtered, and anhydrous ethanol was added at a volume ratio of 1:4 to the remaining gel solid (remaining gel solid: anhydrous ethanol = 1:4). After three deionized water centrifugal washes, a Cu(OH)2 blue precipitate was obtained. The precipitate was placed in a vacuum drying oven and dried at 100°C for 2 h, then ground and kept warm at 500°C in a vacuum tube furnace for 2 h to finally obtain SnO2@CuO black powder (particle size can be controlled at 400 nm).
[0193] The product obtained in step (2) is a black powder of SnO@CuO core-shell structure with a particle size controllable at 400 nanometers.
[0194] Step (3) Mixing and ball milling of core-shell powder and silver powder:
[0195] The SnO2@CuO powder and silver powder in (2) are configured so as to generate 12% (mass percentage) of SnO2@CuO in the silver matrix, and ball milled at a speed of 150 r / min for 0.5 h to obtain a uniformly mixed composite powder.
[0196] The product obtained in step (3) is a uniformly dispersed silver-based composite powder containing 12% SnO@CuO.
[0197] Step (4) pressing, sintering and extrusion drawing process:
[0198] The composite powder in (3) is loaded into a mold, formed under a pressing pressure of 3600 MPa, and the formed ingot is placed in a sintering furnace and sintered at 860°C for 3 hours to obtain a SnO2@CuO reinforced silver-based composite material sintered ingot; finally, the sintered ingot is densified, extruded, drawn (or rolled) and prepared into a wire (or strip).
[0199] The product obtained in step (4): a sintered body of SnO2@CuO reinforced silver-based composite material, with a density of 98%.
[0200] The final product of Example 1: a wire or strip obtained by densification, extrusion drawing (or rolling), wherein the SnO2@CuO particle size is fine particles, the content is medium 12%, and a relatively balanced state between "conductivity-strength" is minimum; the pressing pressure is extremely high (3600MPa) and the temperature is 860°C, which is conducive to obtaining a high density and fine-grained structure, and the mechanical properties are significantly improved. At the same time, the content of the reinforcing phase is not too high, and the sacrifice of conductivity is relatively controllable; it is suitable for comprehensive occasions that pursue high strength + good conductivity.
[0201] Example 2 (Comparative Example 1) SnO2@CuO particles with a maximum size of 1000 / 1100nm + content of 13%, high temperature sintering
[0202] Similar to Example 1, Example 2 also follows the idea of “preparing SnO2 core→coating CuO shell→mixing with silver powder and forming by powder metallurgy”, changing the specific formula values and process parameters, thereby obtaining a core-shell structure powder and a final silver-based composite material that are slightly different from the previous example in size, content, and sintering temperature.
[0203] Step (1) Preparation of SnO2 powder:
[0204] like Figure 1 The process flow uses polyethylene glycol (PEG) as a template to prepare SnO2 powders of different sizes. First, tetrahydrofuran and deionized water are prepared into a solution in a volume ratio of 2:1, and then 1 mol / L PEG is added and stirred to make the solution transparent to obtain solution A. Tetrahydrofuran and anhydrous ethanol are prepared into a solution in a volume ratio of 1:1, and then 2 mol / L SnCl4·5H2O and 10 mol / L urea are added and stirred to obtain solution B. Finally, solution A is added to solution B with a burette at a rate of 5 ml each time and at intervals of 8 seconds, and stirring is continued for 30 minutes, and ultrasonic dispersion is performed for 20 minutes (ultrasonic frequency is 50 Hz). Finally, the mixed solution was transferred into a hydrothermal autoclave with a polytetrafluoroethylene liner and reacted at 180°C in a forced air drying oven for 50 minutes. After the reaction, it was naturally cooled to room temperature. The precipitated product was collected and washed 8 times by centrifugation with deionized water and anhydrous ethanol, and dried at 60°C in a vacuum drying oven for 8 hours. The above powder was calcined at 400°C in a muffle furnace for 2 hours and then naturally cooled to room temperature to obtain SnO2 powder (particle size can be controlled at 800nm).
[0205] The product obtained in step (1) is SnO powder with a particle size controllable at 800 nanometers.
[0206] Step (2) Preparation of SnO2@CuO core-shell powder:
[0207] The SnO2 powder prepared in (1) and deionized water were placed in a beaker at a ratio of 1:20 and magnetically stirred for 20 min at 30°C. After stirring, CuSO4 powder (SnO2:CuSO4=6:1) was added and magnetic stirring was continued for 8 min until the mixture was uniformly mixed. The beaker was then placed in an ultrasonic cleaner for 20 min. Finally, a 40 mol / L NaOH solution was added dropwise using a pipette at a speed of (10 s / drop). After the solution pH reached 9, stirring was continued for 100 min, the supernatant was filtered, and anhydrous ethanol was added at a volume ratio of 1:4 to the remaining gel solid (remaining gel solid: anhydrous ethanol = 1:4). After three deionized water centrifugal washes, a Cu(OH)2 blue precipitate was obtained. The precipitate was placed in a vacuum drying oven and dried at 100°C for 3 h, then ground and kept warm at 600°C in a vacuum tube furnace for 1 h to finally obtain SnO2@CuO black powder (particle size can be controlled at 1000 nm).
[0208] The product obtained in step (2) is a black powder of SnO core@Cu shell O structure with a particle size controllable at 1000 nanometers.
[0209] Step (3) Mixing and ball milling of core-shell powder and silver powder:
[0210] The SnO2@CuO powder and silver powder in (2) are configured so as to generate 13% (mass percentage) of SnO2@CuO in the silver matrix, and ball milled at a speed of 400 r / min for 1.5 h to obtain a uniformly mixed composite powder.
[0211] The product obtained in step (3) is a CuO-uniformly dispersed silver-based composite powder containing 13% SnO@.
[0212] Step (4) pressing, sintering and extrusion drawing process:
[0213] The composite powder in (3) is loaded into a mold and formed under a pressing pressure of 500 MPa, and the formed ingot is placed in a sintering furnace and sintered at 760°C for 6 hours to obtain a SnO2@CuO reinforced silver-based composite material sintered ingot; finally, the sintered ingot is densified, extruded and drawn to prepare a wire.
[0214] The product obtained in step (4): a sintered body of SnO2@CuO reinforced silver-based composite material, with a density of 98%.
[0215] The final product of Example 2: Wire or strip prepared by densification, extrusion and drawing, in which the SnO2@CuO reinforcing phase particles are larger and the content is slightly higher than that of Example 1, reaching 13%, which is relatively easy to obtain and more suitable for lower equipment requirements; when the larger reinforcing phase particles are distributed in the silver matrix, the surface area of each particle is relatively small, thereby reducing the total interface area, so that the electrons encounter fewer interface obstacles during transmission, which helps to maintain a high conductivity; when the larger particles can be evenly dispersed in the silver matrix and do not form agglomerations or aggregations, the reduced number of interfaces helps to improve conductivity. However, since the SnO2@CuO content is also slightly high and the overall sintering temperature is low, the density and fine grain strengthening are slightly inferior; if the medium mechanical properties and conductivity can be taken into account, and the process threshold is relatively low, the cost is lower, it is an alternative solution for economic scenarios.
[0216] Example 3 (Comparative Example 2) SnO2@CuO particles are larger + 12% content, low pressure and low temperature long sintering, good conductivity, mechanical strength is slightly inferior to Example 1
[0217] Example 3 still revolves around the overall idea of "preparing SnO2 core→coating CuO shell→mixing with silver powder and powder metallurgy forming". Compared with the previous two examples, new adjustments are made in terms of PEG dosage, SnCl4·5H2O and urea concentrations, and subsequent CuSO4 precipitation and calcination temperature, thereby obtaining larger particle size SnO2 (1000nm) and SnO2@CuO (1100nm) core-shell powders.
[0218] Step (1) Preparation of SnO2 powder:
[0219] like Figure 1 The process flow uses polyethylene glycol (PEG) as a template to prepare SnO2 powders of different sizes. First, tetrahydrofuran and deionized water are prepared into a solution in a volume ratio of 2:1, and then 2 mol / L PEG is added and stirred to make the solution transparent to obtain solution A. Tetrahydrofuran and anhydrous ethanol are prepared into a solution in a volume ratio of 1:1, and then 5 mol / L SnCl4·5H2O and 20 mol / L urea are added and stirred to obtain solution B. Finally, solution A is added to solution B with a burette at a rate of 5 ml each time and at intervals of 5 s, and stirring is continued for 40 min, and ultrasonic dispersion is performed for 30 min (ultrasonic frequency is 50 Hz). Finally, the mixed solution was transferred into a hydrothermal autoclave with a polytetrafluoroethylene liner and reacted at 180°C in a forced air drying oven for 50 minutes. After the reaction, it was naturally cooled to room temperature. The precipitated product was collected and washed by centrifugation with deionized water and anhydrous ethanol for 8 times, and dried at 60°C in a vacuum drying oven for 8 hours. The above powder was calcined at 400°C in a muffle furnace for 2 hours and then naturally cooled to room temperature to obtain SnO2 powder (particle size can be controlled at 1000nm).
[0220] The product obtained in step (1) is SnO2 powder with a particle size controllable at 1000 nanometers.
[0221] Step (2) Preparation of SnO2@CuO core-shell powder:
[0222] The SnO2 powder prepared in (1) and deionized water were placed in a beaker at a ratio of 1:20 and magnetically stirred for 25 min at 30°C. After stirring, CuSO4 powder (SnO2:CuSO4=6:1) was added and magnetically stirred for 7 min until the mixture was uniformly mixed. The beaker was then placed in an ultrasonic cleaner for 25 min. Finally, a 40 mol / L NaOH solution was added dropwise using a pipette at a speed of (10 s / drop). After the solution pH reached 7, stirring was continued for 100 min, the supernatant was filtered, and anhydrous ethanol was added at a volume ratio of 1:4 to the remaining gel solid (remaining gel solid: anhydrous ethanol = 1:4). After three deionized water centrifugal washes, a Cu(OH)2 blue precipitate was obtained. The precipitate was placed in a vacuum drying oven and dried at 100°C for 2 h, then ground and kept warm at 650°C in a vacuum tube furnace for 1 h to finally obtain SnO2@CuO black powder (particle size can be controlled at 1100 nm).
[0223] The product obtained in step (2) is a black powder of SnO2@CuO core-shell structure with a particle size controllable at 1100 nanometers.
[0224] Step (3) Mixing and ball milling of core-shell powder and silver powder:
[0225] The SnO2@CuO powder and silver powder in (2) are configured so as to generate 12% (mass percentage) of SnO2@CuO in the silver matrix, and ball milled at a speed of 300 r / min for 1.5 h to obtain a uniformly mixed composite powder.
[0226] The product obtained in step (3): a uniformly dispersed silver-based composite powder containing 12% SnO2@CuO
[0227] Step (4) pressing, sintering and extrusion drawing process:
[0228] The composite powder in (3) is loaded into a mold and formed under a pressing pressure of 550 MPa, and the formed ingot is placed in a sintering furnace and sintered at 860°C for 4 hours to obtain a SnO2@CuO reinforced silver-based composite material sintered ingot; finally, the sintered ingot is densified and extruded to prepare a strip.
[0229] The product obtained in step (4): a sintered body of SnO2@CuO reinforced silver-based composite material, with a density of 98%.
[0230] The final product of Example 3: a wire or strip prepared by densification, extrusion and drawing, in which the SnO2@CuO content in the example with the largest particles is not high (12%), and the sintering temperature is 860°C; due to the large particles and relatively few interfaces, the effect on conductivity is alleviated to a certain extent, but the mechanical enhancement effect is not as good as that of fine particles; it is more suitable for occasions with higher requirements on conductivity but relatively medium enhancement requirements.
[0231] Example 4 (Comparative Example 3) SnO2@CuO medium particle size 500 / 700nm + maximum 15% content, medium-high temperature sintering 820℃, more inclined to high strength and wear resistance, relatively poor conductivity
[0232] Example 4 is similar to the above three examples, and still follows the core route of "preparing SnO2 core→coating CuO shell→mixing with silver powder and powder metallurgy forming". The main difference lies in the readjustment of process parameters to prepare medium-sized SnO2 (500nm) and SnO2@CuO core-shell powder of about 700nm, and to achieve a core-shell content of 15% in the silver matrix, and finally obtain the strip by rolling.
[0233] Step (1) Preparation of SnO2 powder:
[0234] like Figure 1 The process flow is as follows: (1) SnO2 powders of different sizes are prepared using polyethylene glycol (PEG) as a template. First, tetrahydrofuran and deionized water are prepared into a solution in a volume ratio of 2:1, and then 1.5 mol / L PEG is added and stirred until the solution becomes transparent to obtain solution A. Tetrahydrofuran and anhydrous ethanol are prepared into a solution in a volume ratio of 1:1, and then 4 mol / L SnCl4·5H2O and 12 mol / L urea are added and stirred to obtain solution B. Finally, solution A is added to solution B with a burette at a rate of 5 ml each time and at intervals of 6 s, and stirring is continued for 40 min, and ultrasonic dispersion is performed for 20 min (ultrasonic frequency is 50 Hz). Finally, the mixed solution was transferred into a hydrothermal autoclave with a polytetrafluoroethylene liner and reacted at 180°C in a forced air drying oven for 40 minutes. After the reaction, it was naturally cooled to room temperature. The precipitated product was collected and washed 9 times by centrifugation with deionized water and anhydrous ethanol, and dried at 60°C in a vacuum drying oven for 8 hours. The above powder was calcined at 400°C in a muffle furnace for 2 hours and then naturally cooled to room temperature to obtain SnO2 powder (particle size can be controlled at 500nm).
[0235] The product obtained in step (1) is SnO powder with a particle size controllable at 500 nanometers.
[0236] Step (2) Preparation of SnO2@CuO core-shell powder:
[0237] The SnO2 powder prepared in (1) and deionized water were placed in a beaker at a ratio of 1:20 and magnetically stirred for 20 min at 30°C. After stirring, CuSO4 powder (SnO2:CuSO4=6:1) was added and magnetic stirring was continued for 9 min until the mixture was uniformly mixed. The beaker was then placed in an ultrasonic cleaner for 20 min. Finally, a 40 mol / L NaOH solution was added dropwise using a pipette at a speed of (10 s / drop). After the solution pH reached 9, stirring was continued for 90 min, the supernatant was filtered, and anhydrous ethanol was added at a volume ratio of 1:4 to the remaining gel solid (remaining gel solid: anhydrous ethanol = 1:4). After three deionized water centrifugal washes, a Cu(OH)2 blue precipitate was obtained. The precipitate was placed in a vacuum drying oven and dried at 100°C for 2 h, then ground and kept warm at 500°C in a vacuum tube furnace for 2 h to finally obtain SnO2@CuO black powder (particle size can be controlled at 700 nm).
[0238] The product obtained in step (2) is a black powder of SnO2@CuO core-shell structure with a particle size controllable at 700 nanometers.
[0239] Step (3) Mixing and ball milling of core-shell powder and silver powder:
[0240] The SnO2@CuO powder and silver powder in (2) are configured so as to generate 15% (mass percentage) of SnO2@CuO in the silver matrix, and ball milled at a rotation speed of 450 r / min for 0.5 h to obtain a uniformly mixed composite powder.
[0241] The product obtained in step (3) is a uniformly dispersed silver-based composite powder containing 15% SnO2@CuO.
[0242] Step (4) pressing, sintering and extrusion drawing process:
[0243] The composite powder in (3) is loaded into a mold and formed under a pressing pressure of 400 MPa, and the formed ingot is placed in a sintering furnace and sintered at 820°C for 5 hours to obtain a SnO2@CuO reinforced silver-based composite material sintered ingot; finally, the sintered ingot is densified and rolled to prepare a strip.
[0244] The product obtained in step (4): a sintered body of SnO2@CuO reinforced silver-based composite material, with a density of 98%.
[0245] The final product of Example 4: a wire or strip prepared by densification, extrusion and drawing, in which the SnO2@CuO reinforcing phase content is the largest, the mechanical enhancement and wear resistance effects will be more prominent, but the impact on conductivity is also greater; the sintering temperature is 820°C, the time is 5h, and it is rolled into a strip, which is suitable for electrical contacts or high-load environments with particularly high requirements for mechanical properties and wear resistance; if more emphasis is needed on strength, this option can be selected, but the conductivity is relatively weak among the four.
Claims
1. A method for preparing SnO2@CuO reinforced silver-based composite materials by hydrothermal synthesis and powder metallurgy, characterized in that: The method comprises the following steps: S1. SnO2 powder of core material: SnO2 powder is prepared by using polyethylene glycol PEG as a template to prepare SnO2 powder of core material; S2. Deposition synthesis of shell material: Cu(OH)2 powder is generated by hydrothermal method on the surface of SnO2 powder, and then the Cu(OH)2 is calcined to obtain SnO2@CuO powder with core-shell structure; S3. Preparation of composite powder: The core-shell structure of SnO2@CuO powder and silver powder are mixed in proportion and ball-milled to form a uniformly dispersed reinforcing phase in the silver matrix; S4. Forming and sintering: The mixed powder is pressed into a shape and sintered to obtain a sintered blank, and the sintered blank is densified and extruded, drawn or rolled into a SnO2@CuO reinforced silver-based composite material wire or strip.
2. The method for preparing SnO2@CuO reinforced silver-based composite material by hydrothermal synthesis and powder metallurgy according to claim 1, characterized in that: The step S1 uses polyethylene glycol PEG as a template to prepare SnO2 powder, comprising: S1.1 Prepare polyethylene glycol template solution: mix tetrahydrofuran and deionized water in a volume ratio of 2:1, add 0.1-3 mol / L polyethylene glycol PEG, and stir until the solution is transparent to obtain a polyethylene glycol template solution; S1.2 Prepare a tin source solution: mix tetrahydrofuran and anhydrous ethanol in a volume ratio of 1:1, add 1-5 mol / L SnCl4·5H2O and 3-20 mol / L urea, stir evenly, and obtain a tin source solution; S1.3 Mix the polyethylene glycol template solution and the tin source solution: Use a burette to add the polyethylene glycol template solution to the tin source solution at a rate of 5 ml each time and an interval of 3-10 seconds, continue stirring for 15-50 minutes, and then perform ultrasonic dispersion for 10-30 minutes at an ultrasonic frequency of 50 Hz; S1.4 Hydrothermal synthesis reaction: transfer the mixed solution into a hydrothermal reactor with a polytetrafluoroethylene liner, react at 180°C for 30-60 minutes, cool naturally to room temperature after the reaction, collect the precipitated product and wash it with deionized water and anhydrous ethanol by centrifugation for 5-10 times, and dry it in a vacuum drying oven at 60°C for 5-12 hours until it is completely dry; S1.5 Calcination treatment: Calcine the dried powder in a muffle furnace at 300-800°C for 1-3 hours, and cool it naturally to room temperature to obtain SnO2 powder with a particle size that can be controlled between 50nm and 1000nm.
3. The method for preparing SnO2@CuO reinforced silver-based composite material by hydrothermal synthesis and powder metallurgy according to claim 1, characterized in that: The step S2 uses a hydrothermal method to generate Cu(OH)2 and synthesize SnO2@CuO core-shell powder, including the following: S2.1 Preparation of SnO2 powder suspension: Mix the SnO2 powder prepared in step (1) with deionized water in a ratio of 1:20 and stir magnetically at 30°C for 15-30 minutes; S2.2 Add copper source copper sulfate (II) CuSO4 powder: Add CuSO4 powder, the mass ratio of SnO to CuSO4 is 6:1, and continue stirring for 5-10 minutes until the mixture is uniform; S2.3 Adjust the pH value of the solution: add 40 mol / L NaOH solution at a rate of 10 seconds / drop with a pipette, slowly add one drop of NaOH solution with a pipette every 10 seconds, adjust the pH value of the solution to 7-9, and continue stirring for 90-120 minutes; S2.4 Filter the supernatant: add anhydrous ethanol at a volume ratio of 1:4 between the remaining gel solid and anhydrous ethanol, centrifuge and wash 2-5 times to obtain a blue Cu(OH)2 precipitate; S2.5 Drying and grinding: Dry the precipitate in a vacuum oven at 100°C for 1-3 hours; S2.6 Sintering into a core-shell structure: After grinding, keep the mixture in a sintering furnace at 100-850°C for 1-2 hours, and finally cool it naturally to room temperature to obtain SnO2@CuO black powder with a particle size that can be controlled in the range of 80nm-1100nm.
4. The method for preparing SnO2@CuO reinforced silver-based composite material by hydrothermal synthesis and powder metallurgy according to claim 1, characterized in that: The step S3 of preparing the composite powder is to mix the core-shell structured SnO2@CuO powder and the silver powder according to the ratio of 10%-18% SnO2@CuO in the silver matrix, and ball mill at a speed of 50-450r / min for 0.5-1.5 hours to obtain a uniformly mixed composite SnO2@CuO core-shell structure powder.
5. The method for preparing SnO2@CuO reinforced silver-based composite material by hydrothermal synthesis and powder metallurgy according to claim 1, characterized in that: The step S4 of forming and sintering includes the following: The composite powder is loaded into a mold and formed at a pressing pressure of 200-600 MPa. The formed ingot is then placed in a sintering furnace and sintered at 400-860°C for 3-6 hours to obtain a SnO2@CuO reinforced silver-based composite material sintered ingot. The sintered ingot is then densified and prepared into a wire or strip by extrusion, drawing or rolling. The preferred pressing pressure is 400 MPa.
6. The method for preparing SnO2@CuO reinforced silver-based composite material by hydrothermal synthesis and powder metallurgy according to claim 2, characterized in that: In the preparation of SnO2 powder using the S1 template, the preferred amount of polyethylene glycol PEG added in the polyethylene glycol template solution is 0.5 mol / L, the preferred amount of SnCl4·5H2O added in the tin source solution is 3 mol / L, and the preferred amount of urea added is 15 mol / L. The particle size of the synthesized SnO2@CuO powder is 450 nm.
7. The method for preparing SnO2@CuO reinforced silver-based composite material by hydrothermal synthesis and powder metallurgy according to claim 2, characterized in that: The content of SnO2@CuO in the composite powder is 14%, and the ball milling conditions are a rotation speed of 350 r / min and a time of 1 hour; the particle size of the prepared SnO2 powder is preferably 350 nm.
8. The method for preparing SnO2@CuO reinforced silver-based composite material by hydrothermal synthesis and powder metallurgy according to claim 4, characterized in that: The sintering temperature of the ingot is divided into three stages: First sintering: Keep at 400℃ for 1 hour, and the particles will be bonded and connected to the sintering neck at a microscopic level. Second sintering: Keep at 600℃ for 1 hour, the diffusion bonding between powders is deepened, the micropores inside the material are compressed and reduced, and the contact between particles is strengthened; The third sintering: keep the temperature at 860℃ for 1 hour, the high temperature promotes the diffusion of a large number of atoms or ions, achieves more complete densification, greatly reduces the porosity, and forms a uniform and stable reinforcement phase distribution.
9. The method for preparing SnO2@CuO reinforced silver-based composite material by hydrothermal synthesis and powder metallurgy according to claim 4, characterized in that: The density of the sintered green body after densification reaches 98%, the extrusion temperature is 800°C, the extrusion pressure is 600MPa, and it is finally drawn into wire at room temperature.
10. A SnO2@CuO reinforced silver-based composite material, characterized in that: The sintered compact of SnO2@CuO reinforced silver-based composite material has fine particles of SnO2@CuO, a content of 12%, and a density of 98%.
Citation Information
Patent Citations
Preparation method of SnO2-coated CuO reinforced silver-based composite material
CN117210713A
Method for preparing SnO2-coated CuO reinforced silver-based composite material through powder metallurgy method
CN118480709A
Ordered nanoenergetic composites and synthesis method
US20070095445A1
Methods For Production of Metal Oxide Nano Particles With Controlled Properties, and Nano Particles and Preparations Produced Thereby
US20080311031A1
Metal sintering densification and grain dimension control method
WO2020132881A1